Annealing Effects on the Electrical Activation of Si Dopants in InGaAs - Lind, Aaron Gregg; Aldridge, Henry Lee; Bomberger, Cory Carl; Hatem, Chris; Zide, Joshua M. O.; Jones, Kevin Scott (ECS transactions, 2015)
The thermal stability of Si dopants incorporated during growth and via ion implantation was investigated as a function of annealing time and temperature. Ion implanted samples show a maximum achievable doping concentration of 1.4×1019 cm-3. Growth doped samples exhibit higher post growth electrical activations than achievable in ion implanted samples but subsequent thermal processing at 750°C for 10 minutes is shown to deactivate heavily doped (3×1019 cm-3) MBE doped substrates to the same active doping concentration of 1.4×1019 cm-3 suggesting a common thermodynamic limit to Si activation in InGaAs.